Improving the Effectiveness of Legal Instruments in Addressing Environmental Pollution to Protect Public Health - Herisasono, Adi; Hardyansah, Rommy; Nuraini, Reny; Vitrianingsih, Yeni (Journal of Social Science Studies, 2021)
This research discusses the effectiveness of legal instruments in regulating environmental pollution and its effect on public health. While there are various regulations designed to protect the environment, the main challenge faced is in inconsistent implementation and legal enforcement. Environmental pollution, which is often uncontrolled, has a direct impact on the quality of public health. This research shows that while legal frameworks such as the Clean Air Act in the United States have shown success in reducing pollutant emissions, weak legal enforcement still hinders the achievement of optimal results. Therefore, there is a need for improved capacity of legal enforcement agencies, stricter oversight, and cross-sector collaboration to strengthen the effectiveness of existing regulations. This research suggests the need for legal counseling and strengthening transparency in the legal enforcement process to ensure the sustainability of public health protection.